Improving 7th-grade junior high school mathematics achievement through numbered heads together - Astuti, Nuryani Dwi; Pusporini, Widowati (Psychology, Evaluation, and Technology in Educational Research, 2021)
The purpose of this study was to improve the mathematics learning outcomes of class VII A students with the Numbered Heads Together (NHT) cooperative learning model on the triangle material at SMP Taman Dewasa Ibu Pawiyatan Yogyakarta. This type of research is classroom action research, while the method in this research is quantitative by collecting data through documents and tests. The subjects of this study were 21 students of class VII-A. The test instruments used were the pretest and posttest (evaluation questions in cycle I and cycle II) consisting of 20 multiple-choice questions. The data analysis technique of the mathematics learning achievement test was carried out by calculating the class average score. The results showed that there was an increase in mathematics learning achievement. This is indicated by an increase in the average percentage of student mathematics learning outcomes which increased from an average initial value of 48.33 to 67.86 in the first cycle and in the second cycle to 75.93. So it can be concluded that the Numbered Heads Together (NHT) cooperative learning model can improve the mathematics learning outcomes of class VII A students on triangle material.